Implementation of The AHP Method in Decision Support Systems for Granting Disposal Permits Household Liquid Waste in Makassar City - Ismail, Ismail; Tahir, M Afdal (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2023)
The permit for the disposal of restaurant liquid waste is carried out by the Makassar City Environment Agency. The process of granting permits is carried out by determining eligibility standards with a prediction system without using standardized assessment criteria so that the final determination of granting permits is not accurate and precise. Staff at the Makassar City Environmental Agency are still handwriting the permit issuance which of course takes a long time. The purpose of the study was to develop a permit assessment system with standard computer-based criteria with the concept of a decision support system. The assessment process for determining the feasibility uses the AHP method to calculate the value of each criterion. Decision making presents a hierarchical relationship between factors, attributes, characteristics or alternatives in the decision-making environment. The parameters for evaluating the feasibility of restaurant quality standards are PH 6-9 Mg/L, BOD 100 Mg/L, SS 100 Mg/L, oils and fats 10 mg/L. The application of the AHP method to the decision support system for granting a waste disposal permit results in a qualifying or non-passing category. The final decision of the system greatly facilitates the leadership of the Environmental Agency to determine the granting of permits.